Comparison of Manual, Femtosecond Laser, and Precision Pulse Capsulotomy Edge Tear Strength in Paired Human Cadaver Eyes - Thompson, Vance M; Berdahl, John P; Solano, Joel M; Chang, David F (Ophthalmology (Rochester, Minn.), 2016)
To compare the anterior lens capsulotomy edge tear strength created by manual continuous curvilinear capsulorhexis (CCC), femtosecond laser capsulotomy (FSLC), and a new automated precision pulse capsulotomy (PPC) device. A 3-arm study in paired human cadaver eyes. A total of 44 eye specimens from 22 donors in the United States. Capsulotomy was performed in all eye specimens using manual CCC, a femtosecond laser (LenSx, Alcon, Fort Worth, TX), or an automated PPC device (Zepto, Mynosys Inc., Fremont, CA). The first study arm consisted of 8 pairs of eyes in which 1 eye received PPC and the fellow eye received FSLC. The second study arm consisted of 8 pairs of eyes, with 1 eye receiving PPC and the fellow eye receiving manual CCC. The third study arm consisted of 6 pairs of eyes, with 1 eye receiving a manual CCC and the fellow eye receiving FSLC. After phacoemulsification, 2 capsulotomy edge retractors attached to force transducers were used to stretch the capsulotomy edge of each eye and to measure the resisting force until the capsulotomy edge was torn. Capsulotomy edge tear strength in millinewtons. The PPC edge tear strength was greater than that of FSLC for all 8 pairs of eyes by an average factor of 3.1-fold (PPC mean 73.3±24.9 mN vs. femtosecond laser mean 26.1±6.8 mN; P = 0.012, Wilcoxon matched-pairs, signed-ranks test). The PPC tear strength was greater than that of manual CCC for all 8 pairs of eyes by an average factor of 4.1-fold (PPC mean 95±35.2 mN vs. manual CCC mean 29.1±23.1 mN; P = 0.012, Wilcoxon matched-pairs signed-ranks test). There was no significant difference in the tear strength of capsulotomies produced by manual CCC (mean 21.3±4.9 mN) and FSLC (mean 24.5±11.4 mN) (P = 0.75, Wilcoxon matched-pairs signed-ranks test). The strength of the PPC capsulotomy edge was significantly stronger than that produced by femtosecond laser or manual CCC.